PERSEPSI WAJIB PAJAK DI WILAYAH TANGERANG TERHADAP DIGITALISASI PELAPORAN PAJAK - Louis, Nadya Regina; Ariyanto, Stefanus (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract - The aim of this study is to examine the taxpayer perception on the digitalization of tax reporting system using e-filing application in Tangerang area. The study uses usefulness, user satisfaction, ease of use and security/confidentiality perceptions as proxies to the taxpayer perception. Samples of this study are taken using convenience sampling method consist of 106 respondents in Tangerang area, analysed using multiple linear regression method. The result of this study reveals that usefulness and user satisfaction perception have significant impact on taxpayer perception on using e-filing system, while ease of use and security/confidentiality perception don't have significant impact on taxpayer perception on using e-filing system. Keywords: E-Filing; Tax Digitalization; Taxpayer Perception